The causes of students\' irregularities in class formation at the beginning of each semester in medical sciences universities - Aram Tirgar; Seyd Hossein Mousavie Anijdan; Mostafa Pouyakian; Khodabakhsh Javanshir; Iraj Alimohammadi; Zahra Aghalari (Babol University of Medical Sciences, 2020)
BACKGROUND AND OBJECTIVE: Holding the classes in the first weeks of the official semester is one of the main problems for the university education system. This study aimed to determine assessing the causes of students' irregularities in class formation at the beginning of each semester in medical sciences universities. METHODS: This cross-sectional study was conducted at three universities of Babol, Shahid Beheshti and Iran University of Medical Sciences, on two groups of students, those who attended the first classes of semester and those who missed the classes; available sampling method was used to select participants. The researcher-made questionnaires were used to collect data, including students' personal and educational information, students' viewpoints on the reasons for absenteeism during the first classes of the semester, questions about their familiarity with absenteeism codes and regulations, and their viewpoints on canceling classes at the first days of semester. FINDINGS:The viewpoints of two groups of present and absent students (218 and 130 students, respectively) at classes on the first week of the semester, were analyzed using scores 1-5 in the Likert scale, and indicated that the main reason for the students attending at their first classes of the semester was the importance of specialized courses (4.16±0.94) and teachers' emphasis (4.13±0.96). The most important factors for the students' absence were their experience of canceling first classes of previous semester (3.51±0.95) and students not paying attention to timely attend the first sessions (3.22±1.01). T-test showed that there was a significant direct relationship between students' age and their timely attendance at the beginning of the semester (p=0.035). CONCLUSION: The presence or absence of students at classes on first days of new semester is influenced by various factors and actions taken by influential individuals such as educational staff and faculty members.